ASPECTOS COMPUTACIONAIS E DE MERCADO DA AVALIAÇÃO DA SEGURANÇA DINÂMICA DE SISTEMAS ELÉTRICOS DE POTÊNCIA - Aronés, Manfred Fritz Bedriñana (2003)
In this work, different methodologies for the dynamic security assessment of electric energy systems, the calculation of preventive control measures and the quantification of the economic impact of the generation rescheduling, are used. For the dynamic security assessment the following modules have been adopted: initial data processing and generation of the list of contingencies, processes manager, dynamic selection of contingencies, dynamic assessment of contingencies and monitoring of the dynamic security. The processes of selection and dynamic assessment of contingencies use analysis of the angular transient stability and are controlled by the processes manager module in a distributed processing environment using C++ Builder and CORBA architecture. Classification and ranking of the contingencies are performed with the contingencies selection module which uses the concept of transient energy margin. For the dynamic assessment of the contingencies is used the analysis of the angular transient stability whereas the module of dynamic security monitoring determines the system security. Power system preventive measures are defined by establishing the maximum generation limits computed with fast methods, without use of sensibilities. With the preventive economic dispatch has been measured the economic impact considering only the active power based on the linearization of the problem which is solved with the simplex primal-dual linear programming method, this module takes into account aspects of congestion, transmission active power losses and marginal costs. Load shedding option is considered when it is detected a deficit of active power generation as a result of the preventive measures. The integrated methodology has been implemented in an interactive computer program in a local area network of personal computers under Windows operating system and coded in C++ language. Two test power systems, Anderson-Fouad (WSCC) of 3 generators 9 buses and a configuration of the Brazilian south-southeast system of 46 generators 320 buses, have been used in the simulation of the proposed methodology. An analysis of the test results indicate the level of dynamic security and the cost involved in the improvement of the power system dynamic security.